2019
DOI: 10.1039/c9cc03024g
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the active sites of Ni–Fe phosphide/metaphosphate for efficient oxygen evolution under alkaline conditions

Abstract: The highly active and stable oxygen evolution reaction (OER) performance of Ni–Fe phosphide/metaphosphate (Ni1−xFex-P/PO3) can originate from in situ generated Fe doped γ-NiOOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(40 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…[1][2][3][4][5][6] However,t he benchmark hydrogen evolution reaction( HER) suffers from sluggish reactionk inetics owing to additional water dissociation.M any efforts have been devoted to exploring different catalytic systems and the synthesis of high-performance catalysts for improvingt he HER. 2H 2 + O 2 )i se nvisioned to satisfy the globald emandf or clean and renewable energy,a ttracting significant attentionb ecause of its potential to replace fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] However,t he benchmark hydrogen evolution reaction( HER) suffers from sluggish reactionk inetics owing to additional water dissociation.M any efforts have been devoted to exploring different catalytic systems and the synthesis of high-performance catalysts for improvingt he HER. 2H 2 + O 2 )i se nvisioned to satisfy the globald emandf or clean and renewable energy,a ttracting significant attentionb ecause of its potential to replace fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…2H 2 + O 2 )i se nvisioned to satisfy the globald emandf or clean and renewable energy,a ttracting significant attentionb ecause of its potential to replace fossil fuels. [1][2][3][4][5][6] However,t he benchmark hydrogen evolution reaction( HER) suffers from sluggish reactionk inetics owing to additional water dissociation.M any efforts have been devoted to exploring different catalytic systems and the synthesis of high-performance catalysts for improvingt he HER. [7][8][9][10] Notably,t he use of transition metal dichalcogenides has been intensively investigated by Rao and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…As the number of CV scans increased, the oxidation and reduction peaks of the Ni foil were shifted to a positive voltage. In general, it has been reported that the oxidation-reduction peak shifts to a positive voltage value until a stable phase is obtained on the surface of the NF in the OER and that it takes approximately 100 cycles for the peaks to stabilize [17]. However, no potential change was observed in the MnO/NF, Fe2O3/NF, and Fe2O3-MnO/NF electrodes assembled here, despite cycling.…”
Section: Electrochemical Measurementsmentioning
confidence: 62%
“…Qiao's group reports the free‐standing single crystalline structure is advantageous for designing robust OER electrocatalyst due to their rigid and defect free structure . Vertically aligned NiFe Hydroxide grown on nickel foam via a facile hydrothermal method was tested in 1 M KOH at different current density of 10, 50 and 100 mA cm −2 achieving an overpotential of 267, 276 and 288 mV, respectively.…”
Section: Self‐supported Oer Catalystmentioning
confidence: 99%